Local Mass and Heat Transfer on a Turbine Blade Tip - P. Jin; R. J. Goldstein (International Journal of Rotating Machinery)
Local mass and heat transfer measurements on a simulated high-pressure turbine blade-tip surface are conducted in a linear cascade with a nonmoving tip endwall, using a naphthalene sublimation technique. The effects of tip clearance (0.86–6.90% of chord) are investigated at various exit Reynolds numbers (4–7 × 105) and turbulence intensities (0.2 and 12.0%).